Cultural differences are reflected in variables associated with carer burden in FTD: A comparison study between India and Australia - Mekala,Shailaja (2013)
ABSTRACT There is great need to understand variables behind carer burden, especially in FTD. Carer burden is a complex construct, and its factors are likely to vary depending on the type of dementia, carer characteristics and cultural background. Objective: The present study aimed to compare profiles and severity of carer burden, depression, anxiety and stress in carers of FTD patients in India in comparison to Australia; to investigate which carer variables are associated with carer burden in each country. Methods: Data of 138 participants (69 dyads of carers-patients) from India and Australia (India, n=31; Australia, n=38). Carer burden was assessed with the short Zarit Burden Inventory; carer depression, anxiety and stress were measured with the Depression, Anxiety and Stress-21. Dementia severity was determined with the Frontotemporal Dementia Rating Scale (FTD-FRS), and a range of demographic variables regarding the carer and patient were also obtained. Results: Overall, levels of carer burden were not significantly different across India and Australia, despite more hours delivering care and higher dementia severity in India. Variables associated with burden, however, differed between countries, with carer depression, anxiety and stress strongly associated with burden in India. By contrast, depression, stress, and dementia severity were associated with burden in Australia. Conclusion: This study demonstrated that variables associated with carer burden in FTD differ between cultures. Consequently, cultural considerations should be taken into account when planning for interventions to reduce burden. This study suggests that addressing carers' skills and coping mechanisms are likely to result in more efficacious outcomes than targeting patient symptoms alone.